Desegregation in Little Rock : executive order 10730 - Bryan, Bethany (America's most important documents., 2019)
Examines events leading up to the the order for desegregation in Little Rock, Arkansas in 1957. Discusses notable figures both for and against desegregation and the enduing legacy that events in Little Rock have today. Includes color photographs, a glossary, and further resources.